Gout and risk of knee replacement for severe knee osteoarthritis in the Singapore Chinese Health Study. Issue 12 (December 2017) - Teng, G.G.; Leung, Y.Y.; Ang, L.-W.; Yuan, J.-M.; Koh, W.-P.
Summary: Objective: While cross-sectional and retrospective case–control studies suggest that gout is associated with knee osteoarthritis (KOA), no prospective study has evaluated the risk of total knee replacement (TKR) for KOA in association with gout. We prospectively evaluated the association between gout and the risk of TKR due to severe KOA. Design: We used data from the Singapore Chinese Health Study (SCHS), a prospective cohort with 63, 257 Chinese adults aged 45–74 years at recruitment (1993–1998). Self-report of physician-diagnosed gout was enquired at follow-up I interview (1999–2004) from 52, 322 subjects. TKR cases for KOA after follow-up I were identified via linkage with nationwide hospital discharge database through 31 December 2011. Multivariable Cox proportional hazards regression model was applied with adjustment for potential risk factors of KOA. Results: Among 51, 858 subjects (22, 180 men and 29, 678 women) included in this analysis, after average 9.7 follow-up years, there were 1, 435 cases of TKR. Gout was associated with 39% higher risk of TKR in women [hazard ratio (HR) 1.39; 95% confidence interval (CI) 1.08–1.79] but not in men (HR 0.78; 95% CI 0.49–1.23). The positive gout-TKR association in women remained after excluding participants with self-reported history of arthritis (HR 1.57; 95% CI 1.04–2.37). This association was stronger in women who were lean (body mass index [BMI] < 23 kg/m 2 ) (HR 2.17; 95% CI 1.30–3.64) compared to their heavier counterparts ( P interaction = 0.016). Conclusion: Gout is associated with risk of severe KOA, especially in lean women, suggesting the crystal arthritis may play a role in the pathogenesis or progression of OA.